The Status of Higher Engineering Education in India & Challanges Ahead - Panse, Meena (Journal of Engineering Education Transformations, 1990)
Ever since the first five year plan the primary objective of Govt. of India has been rapid development of Science & Technology & its application to the growth of economy & welfare of our masses. The Govt's commitment to Science & Technology was enunciated in the 'National Science & Technology Policy Resolution' which was adopted by Parliament in 1958.